2021
DOI: 10.1016/j.jamcollsurg.2021.05.009
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Peritoneal Staging for Pancreatic Ductal Adenocarcinoma Using Mutant KRAS Droplet-Digital Polymerase Chain Reaction: Results of a Prospective Clinical Trial

Abstract: BACKGROUND: Pancreatic ductal adenocarcinoma (PDAC) is an aggressive malignancy with predilection for peritoneal dissemination. Accurate peritoneal staging is imperative for treatment recommendations, as one-third of patients develop peritoneal recurrence after resection. Because >90% of PDAC tumors harbor mutant KRAS (mKRAS), we sought to determine feasibility of mKRAS DNA detection in peritoneal lavage (PL) fluid using droplet-digital polymerase chain reaction (ddPCR) via a prospective trial. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 18 publications
1
7
0
Order By: Relevance
“…Recently, Yonkus et al demonstrated a significant association between pCEA/pCA 19–9 and positive abdominal metastatic findings, such as radiographically invisible hepatic or peritoneal metastasis in patients with PDAC. 18 However, the authors also concluded that the prognostic impact of pCEA/pCA 19–9 remains controversial. One strength of the present study is the association of pCA 19–9 with peritoneal recurrence, even in patients with HEP − PER−CY−, whereas patients with elevated levels of both pCA 19–9 and sCA 19–9 were found to be more likely to develop hepatic recurrence.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Recently, Yonkus et al demonstrated a significant association between pCEA/pCA 19–9 and positive abdominal metastatic findings, such as radiographically invisible hepatic or peritoneal metastasis in patients with PDAC. 18 However, the authors also concluded that the prognostic impact of pCEA/pCA 19–9 remains controversial. One strength of the present study is the association of pCA 19–9 with peritoneal recurrence, even in patients with HEP − PER−CY−, whereas patients with elevated levels of both pCA 19–9 and sCA 19–9 were found to be more likely to develop hepatic recurrence.…”
Section: Discussionmentioning
confidence: 99%
“…In patients with PDAC, recent advances in molecular biochemistry have also enabled the detection of minimal residual disease in the peritoneal lavage fluid with superior sensitivity to conventional cytology 16,17 . Even yet, tumor markers in peritoneal lavage fluid have been rarely evaluated, and their clinical utility remains controversial 18,19 …”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations